Diagnostic Accuracy of Doppler Ultrasound in Detection of Portal Vein Thrombosis in Patient with Hepatocellular Carcinoma Taking Computed Tomography (CT) as a Gold Standard - Mehwish Imtiaz, Nabeela Awan, Esha Habib Butt, Zubda Najam, Sana Noor, Waqar Mushtaq, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Portal vein thrombosis (PVT) is a serious complication in hepatocellular carcinoma (HCC) that alters staging and impacts treatment decisions. Although Doppler ultrasound is widely used due to its availability and safety, its diagnostic accuracy remains variable compared to contrast-enhanced computed tomography (CT), the current reference standard. Objective: To evaluate the diagnostic accuracy of Doppler ultrasound in detecting portal vein thrombosis among hepatocellular carcinoma patients, using CT as the gold standard. Methods: A cross-sectional analytical study was conducted on 185 patients diagnosed with hepatocellular carcinoma at Punjab Rangers Hospital from 12 January 2023 to 12 August 2023. All participants underwent both Doppler ultrasound and contrast-enhanced CT. CT was considered the gold standard for confirming PVT. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall diagnostic accuracy of Doppler ultrasound were calculated. Results: Out of 185 patients, 70 were confirmed to have PVT on CT. Doppler ultrasound detected PVT in 65 patients, of which 60 were true positives and 5 were false positives. It failed to detect PVT in 10 patients (false negatives). True negatives were 110. The sensitivity of Doppler ultrasound was 85.7%, specificity was 95.6%, positive predictive value (PPV) was 92.3%, negative predictive value (NPV) was 91.7%, and the overall diagnostic accuracy stood at 91.9%. Conclusion: Doppler ultrasound showed high diagnostic accuracy in detecting portal vein thrombosis among patients with hepatocellular carcinoma, with a sensitivity of 85.7% and specificity of 95.6%. It can serve as a valuable screening tool, especially in settings where CT is not immediately available. However, CT remains essential for definitive diagnosis and staging. Keywords: PVT, CT, Patients, Diagnosis, Carcinoma